The association of stressful events and psychiatric morbidity in pregnant women - Esper, Larissa Horta; Furtado, Erikson Felipe (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2010)
The scientific literature points out the occurrence of relevant associations between stressful experiences and mental health problems among pregnant women. The objective of this study was to analyze the relationship between stressful events and psychiatric morbidity in the third trimester of pregnancy. The study has a clinical, epidemiological, observational, cross-sectional design performed on a sample of 449 pregnant women recruited in a sequential and random fashion at a public maternity hospital in Ribeirão Preto (São Paulo). Data collection was performed using the following instruments: one structured questionnaire, aiming at obtaining socio-demographic data, clinical history of the pregnancy and of the womans health, a questionnaire on psychiatric morbidity (QMPA) and a semi-structured interview for recent life events (IRLE). All participants had experienced stressful events (m=5; sd=2.2; min=1-max=14) with the health category being the most frequent (99.1%) and the most common events being unwanted pregnancy (60.58%; n=272) and average financial burden (31.85%; n=143). The total number of stressful events had a positive and significant correlation to symptoms and emotional complaints of the women (p<0.01). When the categories were evaluated separately, "finances" had the strongest relationship (p<0.01). Results show that women experience many stressful events during pregnancy, and that there is a positive correlation between stressful events and psychiatric symptoms.